PRDM16 Inhibits Cell Proliferation and Migration via Epithelial-to-Mesenchymal Transition by Directly Targeting Pyruvate Carboxylase in Papillary Thyroid Cancer - Liu, Wan-Lin; Guan, Qing; Wen, Duo; Ma, Ben; Xu, Wei-Bo; Hu, Jia-Qian; Wei, Wen-Jun; Li, Duan-Shu; Wang, Yu; Xiang, Jun; Liao, Tian; Ji, Qing-Hai (Frontiers in Cell and Developmental Biology, 2021)
Positive regulatory domain containing 16 (PRDM16) has been implicated in multiple biological processes. It is not yet clear whether PRDM16 is involved in the tumor progression of papillary thyroid cancer (PTC). We measured PRDM16 expression level in PTC tissues by qRT-PCR and analyzed its relationship with clinical characteristics in both Fudan University Shanghai Cancer Center (FUSCC) and The Cancer Genome Atlas (TCGA). We evaluated the function of PRDM16 in PTC cells both in vivo and in vitro. We identified a direct downstream target of PRDM16, pyruvate carboxylase (PC), by RNA sequencing, rescue experiments, luciferase assays and chromatin immunoprecipitation assays. PRDM16 was downregulated in PTC tissues and was significantly related to lymph node metastases and extrathyroid extension in both FUSCC and TCGA cohorts. Overexpression of PRDM16 attenuated the proliferation and migration of PTC cells by inhibiting the epithelial to mesenchymal transition (EMT) process, which was PC dependent. PRDM16 could directly bind to PC promoter and inhibit its expression. The mRNA expression levels of PRDM16 and PC were negatively related in PTC tissues. In conclusion, PRDM16 exhibited an antitumor effect and inhibited EMT in PTC by directly binding to the PC promoter. PRDM16 may be a novel therapeutic target in PTC.